Assembly Sequence Planning for Products with Enclosed Shell - Yan Song; Juan Song; Zhihong Cheng (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Aiming at the special structure of products with enclosed shell, the limitations of the usual methods are analyzed and concepts of axial subassembly and radial subassembly are proposed, the subassemblies are identified base on the adjacent matrix and interference matrix. A new kind of assembly relation matrix with the subassembly information is proposed to express the assembly model，the assembly transition probability in the ant colony algorithm is modified based on the assembly relation matrix and assembly precedence relations. The assembly sequence of products with enclosed shell can be planned rapidly with the algorithm aforementioned. Finally, the effectiveness was verified by an example.